Combining FES and Exoskeletons in a Hybrid Haptic System for Enhancing VR Experience - L. Buatier de Mongeot; E. Galofaro; F. Ramadan; E. D'Antonio; F. Missiroli; N. Lotti; M. Casadio; L. Masia (IEEE, 2023)
Robotic technology and functional electrical stimulation (FES) have emerged as highly effective rehabilitative techniques for individuals with neuromuscular diseases, showcasting their ability to restore motor functions. Within the proposed study, we developed and tested a new hybrid controller combining an upper-limb exoskeleton with FES to enhance haptic feedback when performing task-oriented and bimanual movement, like pick-and-place, in a virtual environment. We investigated the performance of the proposed approach on eight unimpaired participants providing haptic feedback either only by the exoskeleton or by the hybrid system. The hybrid control presents two different modalities, assistive and resistive, to modulate the perception of the load. FES intensity is calibrated to the subjects’ biomechanical properties and it is adjusted in real-time according to the real-time motion of the upper limbs. Experimental results highlighted the ability of the hybrid control to improve kinematic performance: in both hybrid modalities subjects reduced the target matching error(values between 0.048±0.007 m and 0.06±0.006 m) without affecting the normal motion smoothness (SPARC values in the hybrid conditions range from −2.58±0.12 to −3.30±0.13). Moreover, the resistive approach resulted in greater metabolic consumption (1.04±0.03 W/kg), indicating a more realistic experience of lifting a virtual object through FES that increased the perceived weight. The innovation in our hybrid control relies on the modulation of muscular activation during manipulation tasks, which could be a promising approach in the clinical treatment of neuromuscular diseases.